Letter in response to 'The conceptual model of advanced practice does include research' - Smith, T.; Harris, J.; Woznitza, N.; Maresse, Sharon; Sale, C. (John Wiley & Sons, 2015)
This letter refutes the suggestion made the authors of other letters to the Editor that the proposed model of the characteristics of advanced practitioners excludes research International Journal of Experimental Pathology